Multiple Eruptive Pyogenic Granulomas on the Proximal Nail Folds Following Cast Immobilization: A Case Report with Nail Unit Ultrasound Findings - Daniel Lopez-Castillo; Laia Curto-Barredo; Júlia M. Sánchez-Schmidt; Ramon M. Pujol (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)